Diclofenac does not reduce the risk of acute pancreatitis in patients with primary sclerosing cholangitis after endoscopic retrograde cholangiography. Issue 4 (1st May 2020) - Koskensalo, Vilja; Tenca, Andrea; Udd, Marianne; Lindström, Outi; Rainio, Mia; Jokelainen, Kalle; Kylänpää, Leena; Färkkilä, Martti
Abstract : Background: The European Society of Gastrointestinal Endoscopy recommends rectal indomethacin or diclofenac before endoscopic retrograde cholangiopancreatography (ERCP) to prevent post‐ERCP pancreatitis. However, data on the prophylactic effect in patients with primary sclerosing cholangitis (PSC) are lacking. Methods: This was a retrospective case‐control study. In 2009–2018, a total of 2000 ERCPs were performed in 931 patients with PSC. Case procedures ( N  =   1000 after November 2013) were performed after administration of rectal diclofenac. Control procedures ( N  =   1000 before November 2013) were performed with the same indication but without diclofenac. Acute post‐ERCP pancreatitis and other ERCP‐related adverse events (AEs) were evaluated. Results: Post‐ERCP pancreatitis developed in 49 (4.9%) procedures in the diclofenac group and 62 (6.2%) procedures in the control group ( p  =   0.241). No difference existed between the groups in terms of the severity of pancreatitis or any other acute AEs. The risk of pancreatitis was elevated in patients with native papilla: 11.4% in the diclofenac group and 8.7% in the control group ( p  =   0.294). In adjusted logistic regression, diclofenac did not reduce the risk of pancreatitis (odds ratio (OR) = 1.074, 95% confidence interval 0.708–1.629, p  =   0.737). However, in generalised estimation equations with the advanced model, diclofenac seemed to diminish the risk of pancreatitis (OR = 0.503) but not significantly ( p  =   0.110). Conclusion: In this large patient cohort in a low‐risk unit, diclofenac does not seem to reduce the risk of post‐ERCP pancreatitis in patients with PSC. The trend in the pancreatitis rate after ERCP is decreasing. The evaluation of the benefits of diclofenac among PSC patients warrants a randomised controlled study targeted to high‐risk patients and procedures.